Antimicrobial Activity of Pomegranate Peel and Its Applications on Food Preservation - Jing Chen; Chunling Liao; Xiaolu Ouyang; Ibrahim Kahramanoğlu; Yudi Gan; Mingxi Li (Journal of Food Quality)
Pomegranate (Punica granatum L.) fruit is being cultivated since the civilization is known, and its production and consumption have been increased since the last century due to the scientific confirmation of its health benefits. Pomegranate fruits, fruit juice, its seeds, and peels are known to have higher contents of bioactive compounds, viz., phenolic acids, flavonoids, and hydrolysable tannins. The peels of pomegranate fruits are the major by-products produced during food processing of pomegranate enriched in antioxidants and broad-spectrum antimicrobial agents and can prevent food deterioration even. This health potential of pomegranate is known to vary significantly upon the varieties, growing conditions, cultivation practices, stages of the development, and the extraction methods. Herein, the biochemical composition of the pomegranate peel extract (PPE), its efficacy in food preservation, and antimicrobial activities are discussed to provide a comprehensive guide for farmers, food processing, and storage sectors and academia.